Pengembangan Asesmen Pembelajaran Berbasis Game pada Mata Pelajaran IPA Kelas VII SMP - Putri, Lini Oxtoria; Zen, Zelhendri; Rayendra, Rayendra; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to develop a game-based learning assessment in science subjects in grade VII junior high school that is valid and practical. This type of research is Research and Development (R&D). The model used in this development research is a 4D model. The 4D model contains 4 (four) stages of development, including define, design, develop, and disseminate. The research data was obtained through questionnaires and validation sheets, then analyzed in a quantitative descriptive manner. The development process of this game-based learning assessment product has involved a validation stage by material and media experts. A science teacher in grade VII of SMP Negeri 5 Linggo Sari Baganti acted as a material expert, while two lecturers from the Department of Curriculum and Educational Technology of Padang State University acted as media experts. The validation results show that this product is considered very valid, both in terms of material content and design. Furthermore, the trial on 18 grade VII students also produced very positive data, with an average score of 4.71 for the practicality category. Based on these results, it can be concluded that this game-based learning assessment product has gone through a good development stage and is ready to be implemented in the learning process